Iluminação pública: normatização de vias e eficiência energética estudo de caso-loteamento Nilo Gonçalves-Alegrete-RS - Antunes, Lucas Eduardo Dorneles (Universidade Federal do Pampa, 2015)
This paper presents a case study related to energy efficiency in public lighting. The site chosen was in the city of Alegrete-RS Airton Senna 2 in the neighborhood, considering that the project deployed there is recent lighting, uniform and has data from the initial project. The work developed by the characterization of the studied area, verification of the regulatory standards framework for public lighting, research and data collection in the field with the help of luminous flow meters, using the methods of measuring detailed mesh according to ABNT 5101. To check the framing of the project on standardization of urban way,scenarios were developed, with the assumption that via should meet the regulatory criteria. In this way were performed the evaluations of these scenarios, with the indication of possible improvements in efficiency as much as energy lumínica. Through simulation with DIALUX software can analyze the framework on Standardization of the cases offered, and comparing both with the European standard EN 13201 as with the Brazilian ABNT 5101. Of the best scenarios observed, economic analyses were conducted, seeking the case with the best cost-benefit ratio. It was also carried out a preliminary analysis of insertion of a photovoltaic system connected to the distribution network where if compared the results achieved in terms of the Time of Return, net present value and internal rate of return of the best configuration with and without the photovoltaic system.
Keywords: Electrical engineering; Energy efficiency; Public lighting; Distributed generation of electric energy; Solar energy; Engenharia elétrica; Eficiência energética; Iluminação pública; Geração distribuída de energia elétrica; Energia solar; CNPQ::ENGENHARIAS::ENGENHARIA ELETRICA